Efgartigimod for the treatment of immune checkpoint inhibitor-associated myocarditis complicated with impending crisis state of myasthenia gravis: a case report - Lu, Mingjia; Muhetaer, Ayikemaier; Su, Chenxi; Dong, Meng; Aili, Kariman; Sha, Jing; Aimudula, Kaidierya; Abudureheman, Kailibinuer; Mamat, Maynur; Li, Hongyan (Frontiers in Immunology, 2025)
Immune checkpoint inhibitor (ICI)-associated myocarditis is a rare yet life-threatening immune-related adverse event (irAE), whose management is even more challenging when complicated by an impending crisis of myasthenia gravis (MG). This article presents a case of a 69-year-old woman with bladder malignancy, coexisting MG, diabetes, hypertension, and coronary artery disease. On day 16 after tislelizumab (PD-1 inhibitor) therapy, she exhibited aggravated MG symptoms, with an impending crisis, alongside asymptomatic ICI-associated myocarditis. Clinical manifestations included generalized fatigue, anorexia, bilateral ptosis, dysarthria, neck and limb weakness, shortness of breath, and dyspnea. Laboratory tests revealed elevated troponin T, troponin I, creatine kinase (CK), creatine kinase–myocardial band (CK-MB), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) levels, suggesting a diagnosis of ICI-associated myocarditis and liver injury. Doppler ultrasound indicated thrombosis in the left calf muscle space. Treatment with efgartigimod (10 mg/kg) significantly improved myasthenic symptoms, with Myasthenia Gravis–Activities of Daily Living (MG-ADL) and Quantitative Myasthenia Gravis (QMG) scores decreasing from 11 to 5 and 26 to 11, respectively. Treatment with prednisone acetate (60 mg once daily) resulted in gradual reductions in myocardial enzymes, troponins, and transaminases. Efgartigimod demonstrated notable efficacy as salvage therapy for ICI-associated myocarditis, myositis, liver injury, and impending crisis of MG. Early recognition and tailored treatment strategies are crucial for improving patient outcomes in such complex cases.